IRSL dating of fast-fading sanidine feldspars from Sulawesi, Indonesia - Li, B.; Zhao, J.-X.; Grün, R.; Aubert, M.; Ramli, M.; Hakim, B; Guo, Y. J.; Brumm, A.; Roberts, G. R.; Saptomo, E. W. (Ancient TL, 2016)
The volcanic origin of the sediments from Sulawesi, Indonesia, provides a particular challenge for luminescence dating due to the dim optically stimulated luminescence (OSL) from quartz, and the high anomalous fading rate in the infrared (IR) stimulated luminescence (IRSL) from feldspars. In this study, we present results of dating the sanidine feldspars from 2 samples taken from an archaeological site (Leang Bulu Bettue) in the Maros karsts of South Sulawesi. We tested the post-IR IRSL (pIRIR) procedures in order to find a stable luminescence signal that is less affected by anomalous fading. It was found that there is a highly variable anomalous fading rate in the IRSL and pIRIR signals for different grains and aliquots, and a low temperature IR stimulation (at 50 ◦C or 100 ◦C) used in a pIRIR procedure cannot completely remove the anomalous fading for the subsequent pIRIR signals. The large uncertainties associated with fading rates prevent the application of fading-correction procedures. We propose a method to obtain reliable De estimates by extrapolation of the relationship between De and laboratory fading rate (g-value). The resultant luminescence ages show consistency with other radiometric age determinations from the site. Our results suggest that a systematic and detailed investigation of the relationship between De and anomalous fading rate for different grains or aliquots is necessary for dating volcanic feldspars.